Apparatus for Measuring the Moment of Inertia of an Object Using a Rotary Encoder - Katman, Ratchanoo; Amthong, Attapon (Burapha Science Journal, 2026)
In this paper, a laboratory apparatus is designed for measuring the moment of inertia. It mainly consists of a rotary encoder and an arduino nano board, which can be used to measure angular displacement of a rotating object. We propose our experimental approaches to achieve the moment of inertia of any objects using a rotary encoder. The experimental results from the encoder are calculated and analyzed in order to compare with the results from theory. Two mathematical models of the frictional torque are presented and investigated. We find that the mathematical model of leads to the results which are in good agreement with the experimental results. Our designed laboratory apparatus is cheap and its components are available in electronics stores. Thus, it is able to be applied in physics laboratory.